Amalan Autonomi dan Akauntabiliti dalam Pengurusan Sekolah Kluster di Malaysia (Sains Humanika, 2012)
This article is pertaining to the concept of autonomy and accountability that exist in cluster schools of excellence as a result of the process of decentralization in the educational system in Malaysia. Therefore, this exploratory study on the practice of autonomy and accountability in management among cluster schools in Malaysia is executed using interviews and document analysis in data gathering. A total of six cluster schools in the first cohort of recognition were selected as the unit of analysis using a purposive sampling. The study shows that in practice the autonomy obtained by cluster schools of excellence was only focused on certain aspects such as planning of activities to boost niche areas,  creating a smooth process of innovation in teaching and learning, and in appointing coaches to train their students in niche areas respectively. cluster schools of excellence also found to be accountable to  stakeholders, particularly in terms of student’s academic excellence. Based on the findings, it can be concluded that the autonomy obtained by cluster schools of excellence, can be classified as guided autonomy  because cluster schools of excellence are still bounded by various rules and regulations.
Keywords: Autonomy; guided autonomy; accountability; cluster schools of excellence